An Analysis of Cohesive Types in An Article of Why I’am No Longer a Second Amendment Absolutist Taken from TIME Magazine - Sukmiarni , Arni (Jurnal Sastra - Studi Ilmiah Sastra, 2019)
This paper aims to report the result of study focusing on an analysis of coheisve types. The method used in this study is a descriptive method. It describes the kinds of cohesive types in the article containing 34 sentences. The data collection was taken by classifying the text into 34 sentences. Then, the number of cohesive items in each sentence were identified and categorized into types and the presupposed of items. The findings show that in the 34 sentences there are 211 ties of cohesive items comprised of 21% of the reference, 3% of the subtitutio, 34% of the conjunction, 26% of the lexical cohesion and 16% of the definite article.. It indicates that the most dominant type of cohesive items used in the article is the conjunction and there is zero for the ellipsis.